KARAKTERISTIK TEPUNG UBI JALAR (Ipomoea batatas L) TERMODIFIKASI SECARA FERMENTASI MENGGUNAKAN KOJI Bacillus subtilis DAN APLIKASINYA PADA PENGOLAHAN PANGAN - Hervelly Velly (Pasundan Food Technology Journal (PFTJ), 2019)
The aim of this study was obtained ratio of wheat flour and modified sweet potato flour that exactly on dried noodle, sweet bread and biscuits which can accepted by consumer.The experimental Randomized Block Design (RBD) was used in this study with one factor and two times replicated. The factor was recearched as between wheat flour and modified sweet potato flour with leves a0 (100% : 0%), a1 (0% : 100%), a2 (5% : 95%), a3 (10% : 90%), a4 (15% : 85%), a5 (20% : 80%), a6 (25% : 75%), a7 (30% : 70%) and a8 (35% : 65%).The result of study indicated that ratio between wheat flour and modified sweet potato flour was significantly effected on texture, flavour and taste of dried noodle, sweet bread and biscuits.The result of organoleptic test for dried noodle, sweet bread and biscuits obtained the best comparison between wheat flour and modified sweet potato flour of a8 (35% flour and 65% modified sweet potato flour. The results analysis of dried noodle was moisture 6,4039%, starch 29,6665 %, protein 6,2191% and cooking loss 18,7121%.The results analysis of sweet bread was mouisture 24,7525%, starch 32,9982% and protein 9,0174%. and the results anaysis of biscuits was mouisture 2,4390%, starch 4,8007% and protein 3,9785%.